AS DISSIMULAÇÕES E INCOERÊNCIAS NA APLICAÇÃO DA QUALIDADE CAUSAS E CONSEQUÊNCIAS - Barbosa, André Ricardo de Alvarenga (2008)
To present research it intends to analyze the possible causes that take to administrators to act her in their organizations in a dissembling way and with the relationship speech x incoherent practice. Still, it also analyzes the consequences of this administration type. Through a wide bibliographical study and application of field researches in companies, executives in management position and consultants, it was possible to analyze the favorable and unfavorable organizational internal atmospheres to the administration for the quality. The researched companies were divided in two groups. One of companies that they possess a negative scenery, with an administration model with dissimulations and incoherences. The second I group with companies that possess a positive scenery, with a model of favorable administration the quality and with great seriousness in whole the process. For the accomplishment of the study they were researched five variables, adaptation and the employees' satisfaction with the training politics and development, elaboration and unfolding of the strategic planning, accompaniment and use of controls, seriousness of the high administration and resistance of the high administration as for the changes. For each variable several indicators they were used. The results were disposed through tables and graphs by company, for variable and soon afterwards being compared the two sceneries, positive and negative, as already mentioned above. The results appear to 1st and 2nd variables as the more critics among all of the companies, contributing to the companies to be more attentive the those two aspects. To 4th variable, Seriousness of the high administration, causes surprise due to the results above the expected. The final considerations approach another aspect of extreme relevance, the ethics in the professional relationships and interpessoais as critical factor of success in the organizations. It is waited with this work to take the high administration of the organizations reflect it on their administration models, considering that these impact in the behaviors and organizational actings